First order reversal curve analysis of nanocrystalline Pd80Co20 alloy films - Cornejo, D. R.; Noce, R. D. [UNESP]; Peixoto, T. R. F.; Barelli, Nilso [UNESP]; Sumodjo, P. T. A.; Benedetti, Assis Vicente [UNESP] (Elsevier B.V. Sa, 2009)
Films of isotropic nanocrystalline Pd80Co20 alloys were obtained by electrodeposition onto brass substrate in plating baths maintained at different pH values. Increasing the pH of the plating bath led to an increase in mean grain size without inducing significant changes in the composition of the alloy. The magnetocrystalline anisotropy constant was estimated and the value was of the same order of magnitude as that reported for samples with perpendicular magnetic anisotropy. First order reversal curve (FORC) analysis revealed the presence of an important component of reversible magnetization. Also, FORC diagrams obtained at different sweep rate of the applied magnetic field, revealed that this reversible component is strongly affected by kinetic effect. The slight bias observed in the irreversible part of the FORC distribution suggested the dominance of magnetizing intergrain exchange coupling over demagnetizing dipolar interactions and microstructural disorder. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Magnetic films and multilayers; Electrodeposition; Anisotropy; Magnetization; Magnetic measurements